(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Over the last three decades, the use of outpatient surgery has been steadily increasing. Simultaneously, there has been an inciting movement to measure and improve healthcare quality and safety. Nevertheless, anaesthesia-related morbidity remains significant. We aimed to evaluate the incidence of intraoperative adverse events (IAEs) occurring during outpatient surgery. METHODS We used data from the Anaesthesia Databank Switzerland (ADS), a voluntary register. We assessed the overall and specific incidence of IAEs, according to a predefined list of technical, cardiovascular, organisational, respiratory, and general incidents in Switzerland between 2000 and 2016. Primary and secondary outcomes were modelled using multi-level logistic regression analysis, and the time trend on the probabilities of events was assessed. RESULTS Between 2000 and 2016, 289,948 outpatient anaesthesia procedures were performed. During this period, the estimated probability of overall intraoperative adverse events decreased from 10.8% to 6.3%, and from 2.3% to 1.4% for technical incidents, from 3.0% to 2.2% for cardiovascular, from 1.6% to 1.3% for organisational, from 0.9% to 0.7% for general, and from 1.1% to 0.7% for respiratory incidents. CONCLUSIONS The occurrence of intraoperative adverse events in ambulatory anaesthesia has continuously decreased between 2000 and 2016. This trend is essentially attributable to a reduction in the incidence of technical, cardiovascular and organisational events.